The formation mechanism of geological disasters on loess fill slopes revealed by the deformation characteristics of remolded loess under different stress paths - Shuran Meng; Shuran Meng; Dunyu Lv; Dunyu Lv; Ru Liu; Mancang Yu; Mancang Yu; Jianyu Zhang; Jianyu Zhang (Frontiers in Earth Science)
In recent years, geological disasters on loess fill slopes have occurred from time to time, which has attracted widespread attention. In order to deeply understand its deformation and failure laws and promote the disaster prevention and mitigation work, this paper takes remolded loess as the research object, systematically explores the effects of three different stress paths (conventional triaxial compression test (CTC), triaxial compression test with constant average principal stress (TC), and triaxial compression test with reduced confining pressure (RTC)) on its mechanical properties, and observes and analyzes its microstructural characteristics by scanning electron microscopy (SEM). The results show that the soil is strain hardening under the CTC path, while it is strain weak hardening under the TC and RTC paths. In the order of CTC, TC, and RTC paths, the shear strength and volume shrinkage of the soil are reduced in turn, and its deformation has both shear reduction and shear expansion plastic deformation. In the order of CTC, TC, and RTC paths, the degree of particle crushing decreases in turn and the pore content increases in turn. It is inferred that in the initial deformation of loess under loading, the soil is compressed and compacted, and its strength is improved to a certain extent. As the loading continues to increase, the deformation rate increases steadily, and the soil deformation develops gradually, which is mainly axial compression deformation, while the lateral bulging deformation is small until it is destroyed. For the deformation behavior in the form of lateral unloading, the soil is maintained in a relatively stable state at the beginning, and the deformation is very small. When the lateral constraint is reduced to a critical state, the structure is completely unstable, and the deformation develops rapidly in a short time until it is destroyed. This study is of great significance for reducing the occurrence of geological disasters on fill slopes in loess areas.